Developing secure attachment through play : helping vulnerable children to build their emotional and social wellbeing - Moore, Joan (Dramatherapist) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Developing Secure Attachment Through Play offers a range of imaginative and engaging play-based activities, designed to help vulnerable young children forge safe attachments with their caregivers. The book focuses on key developmental stages that may have been missed due to challenging life circumstances, such as social-emotional development, object permanence, and physical and sensory development. It also considers pertinent issues including rauma, paration, loss and transition. Chapters explore each topic from a theoretical perspective, before offering a case study that illustrates the theory in practice, and a range of activities to demonstrate the effectiveness of play in developing healthy attachments. Key features of this book include: Eighty activities that can be carried out at home or in educational settings, designed to facilitate attachment and enhance social-emotional development Case vignettes exploring creative activities such as mirroring, construction play, physical play, baby doll play and messy play Scripts and strategies to create a safe and respectful environment for vulnerable children Photocopiable and downloadable resources, including Early Learning Goals, a collection of therapeutic stories and a Transition Calendar By engaging children in these activities, parents, caregivers and practitioners can help the children in their care gain a sense of belonging and develop their self-esteem. Developing Secure Attachment Through Play will be a valuable resource for early years practitioners, adoptive, foster and kinship parents, and therapists and social workers supporting young children"--
Keywords: Attachment disorder in children; Play therapy; Child psychotherapy; EDUCATION / General; EDUCATION / Preschool & Kindergarten; EDUCATION / Special Education / General